Analysis of kinetics of poorly water-soluble drug release from hydrogels based on poly (methacrylic acid) and casein with different crosslinker amount - Markovic Maja D. (Proceedings of the International Symposium on Analytical and Environmental Problems, 2021)
Nowadays, humanity are faced with many challenges which affect health of people all around the globe (such as climate change, new diseases and/or already present ones for which cure has not been found yet – cancer). The efforts of researchers on the field of drug delivery systems bring everyday novel tools for safer and more effective therapy. pH sensitive hydrogels based on poly(methacrylic acid) are recognized as materials with huge potential for controlled release of drugs. The encapsulation and controlled release of many chemotherapeutics is quite challenge due to their poorly water-solubility. In our previous research we overcome this problem by modifying hydrophilic pol(methacrylic acid) with amphiphilic casein and showed that prepared material have potential for encapsulation and controlled release of poorly watersoluble model drug – caffeine (PMAC carriers). In present study we deepened further our research and employed various models: Ritger-Peppas, Higuchi and Kopcha model to analyze how the change of crosslinker amount affect the mechanism of release kinetics of caffeine in medium with pH of 6.8 (which simulated the environment in human intestines). Obtained results showed that only by changing one parameter such as crosslinker amount it is possible to fine tune the type of drug release mechanism, due to which the PMAC carriers would be able to respond to the specific demands of therapy.